Penerapan metode bernyanyi untuk meningkatan hasil belajar siswa pada materi simbol-simbol pancasila kelas 1 tema 3 sub tema 1 - Wahyuni Eka Priyono; Dilon Yordania (Jurnal Pengembangan dan Evaluasi Pendidikan, 2024)
This study aims to identify the learning process using singing method in Pancasila Symbols materials and also the students' improvement on it. The use of inacurate methods could affect the learning process. The materials which are delivered by the proper methods will be much more effective than the ones conducted without the methods. Thus, the learning process needs a solution to repackage the whole process with an interactive and innovative way to deliver the Civic Education to the students. One of which is by singing the song since children are often identical to singing. The implementation of singing method is expected to enhance the students' learning process and create enjoyable atmosphere to learn the materials.This study will be conducted in SD Muhammadiyah which is located in Kecamatan Klojen Kota Malang. The study implies Classroom Action Research (CAR) with quantitative and qualitative approaches. This study is qualitative since it has words as the data along with the analysis. At the same time, this study is also quantitative since it results numbers and will be analyzed using statistics technique.Based on the findings and discussion, it is known that the learning process in Pancasila Symbols using singing method is successfully conducted. This is proven by the median of the observation sheets analysis. The analysis shows that the median is improved from the Cycle 1 which is 79.2% (Good) becomes 87.5% in Cycle 2 (Excellent). The improvement is also proven by the students' output, in the Cycle 1 they get 68.5 as the average, and in the Cycle 2 they get 92.8. Based on the discussion it can be concluded that the results are satisfying since all the indicators have already been achieved.